The level of generalized anxiety among university students (A field study at Tishreen University) - صبيره , فؤاد; تركماني , مي (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The current research aims to identify the level of symptoms of generalized anxiety disorder among a sample of Tishreen University students. The sample consisted of (500) male and female students from Tishreen University students in Lattakia Governorate. The scale which used in this research is symptoms of generalized anxiety disorder, according to the curriculum descriptive. Researcher used statistical methods as following: (T test, Alfa test). The research found that: More than half of the respondents had symptoms of generalized anxiety at an average level (60.4%). There is a difference between the mean of the respondents ’mean responses on the generalized anxiety scale attributable to gender variables, and the college in favor of males, and in favor of theoretical faculty students. There were differences due to the age change in favor of the older age group (26-28 years). In view of the results of the research, a number of proposals were presented, the most important of which are: attention to psychological preparation for students, the use of psychological tests as an objective way to evaluate the status of students, and the preparation of counseling programs related to the problems they are experiencing psychologically during the university stage.